PEMBUATAN FILM DOKUMENTER PADA SUBMATERI TINGKAT KEANEKARAGAMAN HAYATI KELAS X SMA - Khadijah, Siti; Hardigaluh, Basuki; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the feasibility of a documentary film of the fishermen?s fish inventory as a learning media on the sub-material ?The Level of Biodiversity? and to find out the fish species found at the fishing spots of Jungkat village, Mempawah Regency. This study was conducted using the descriptive method with a purposive sampling technique. The data were collected using the triangulation technique. The study was conducted in two steps: (1) documenting the fish inventory process and (2) creating the documentary film. The study found 27 species from 18 families, and they were taken into account as the resource for the documentary film. Six validators of the media feasibility consist of three material experts and three media experts. The average score gained from the media experts? and the material experts? validations is respectively 3,27 and 3,4. The results indicate that the media is valid and suitable to use in teaching and learning process on the grade 10 sub-material ?The Level of Biodiversity.  Keywords: Documentary Film, Inventory, Jungkat